Plasma parameters evolution during conditioning RF discharges in Uragan-2M torsatron - Skibenko, A.I.; Prokopenko, A.V.; Berezhnyj, V.L.; Burchenko, P.Ya.; Krasnyj, V.V.; Kulaga, A.E.; Lesnyakov, G.G.; Lozin, A.V.; Moiseenko, V.E.; Ocheretenko, V.L.; Pavlichenko, O.S.; Pinos, I.B.; et al. (Вопросы атомной науки и техники, 2009)
The results of the plasma parameters optimization measured via two-chord interferometry, radiometry, and the registering of the Нα, CIII, OII lines intensity are discussed. The optimization was realized by variation of RF scenario of the RF power introduction, pressure and magnetic field.